Isolation and Identification of Secondary Metabolites from Etlingera rubroloba Rhizome and Their Biological Activity as Antimicrobial and Antioxidant - Malaka, Muhammad Hajrul; Solo, Dian Munasari; Trinovitasari, Nita; Sahidin, Sahidin (Molekul, 2025)
ABSTRACT. Etlingera is a genus known for its potential medicinal properties. Etlingera rubroloba A.D. Poulsen is a recently identified species within the Etlingera genus found in Southeast Sulawesi. This study aims to isolate and identify secondary metabolite compounds from the methanol extract of the E.rubroloba A.D. Poulsen rhizome and its activity as an antimicrobial and antioxidant. The compound was isolated by using Thin Layer Chromatography (TLC), Vacuum Liquid Chromatography (VLC), and Radial Chromatography (RC) techniques. Isolated compounds were identified by 1H and 13C NMR spectroscopy techniques and compared the data with reference. Antimicrobial tests were carried out on Escherichia coli, Streptococcus mutans, and Candida albicans by broth microdilution method. The antioxidant test was carried out using the 1,1-dipheny1-2-picrylhydrazyl (DPPH) method. Four isolated compounds were successfully isolated : stigmasterol (1); 1,7-diphenyl-6-hepten-3-on; (2); and 1,7-diphenyl-heptan-3-on (3); and sinapyl alcohol diacetate (4). Antimicrobial activity test results extract were active against all bacteria and C. albicans. The results of antioxidant activity test showed that extract, compound 2, 3, and 4 had strong and medium antioxidant activity with IC50 values at 75.05 μg/mL; 201.4 μg/mL; 207.88 μg/mL, and 190.59 μg/mL, respectively. Keywords: antioxidant, antimicrobial, DPPH, Etlingera, isolation